Investigating isomer specific photoprotection in a model plant sunscreen. Issue 8 (10th January 2018) - Horbury, M. D.; Flourat, A. L.; Greenough, S. E.; Allais, F.; Stavros, V. G.
Abstract : Sinapate esters are used throughout the plant kingdom, for example in photoprotection from ultraviolet radiation. Abstract : Sinapate esters are used throughout the plant kingdom, for example in photoprotection from ultraviolet radiation. Sinapate esters are naturally produced in their E -isomeric form; however, upon exposure to ultraviolet radiation, photoisomerization drives Z -isomer formation. To elucidate the photoprotection capacity of E vs. Z forms of sinapate esters, we explore the photochemistry of the model system, Z -ethyl sinapate. Following a novel Z -ethyl sinapate synthesis, we demonstrate that photoprotection is isomer independent. This suggests that, regarding photoprotection, there were no evolutionary pressures for biosynthesis of either isomer.